The Effect of Implementing the Sport Education Model (SEM) on Students’ Motivation in Physical Education (PE) Learning Basketball at State Vocational High School 1 of South Indralaya - Ratno Jamalludin; Dessy Wardiah; Hikmah Lestari (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
Learning motivation is an important factor in the success of Physical Education, Sports, and Health learning, especially in basketball. Learning that is still dominated by conventional methods tends to result in low student participation and motivation. This study aims to determine the effect of the application of the Sport Education Model (SEM) on student learning motivation in PE learning on basketball at State Vocational High School 1 South Indralaya. This study uses a quantitative approach with an experimental method. The research subjects consisted of an experimental class given SEM learning treatment and a control class using conventional learning. The research instrument was a student learning motivation questionnaire. Data analysis was conducted using paired samples t-test and independent samples t-test. The results showed that there was a significant increase in student learning motivation in the experimental class after the implementation of SEM, and there was a significant difference in learning motivation between the experimental and control classes. For data analysis using the t-test dan ANCOVA, showing the results that there was a significant difference with a value of α = 0,05, so that the application of SEM had a real effect on student learning motivation after controlling for covariate variabels. These findings indicate that SEM is more effective than conventional learning in increasing self-motivation ini PE Learning, especially in basketball material. Thus, the Sport Education Model has a positive effect on student learning motivation in PE learning on basketball. The application of SEM is recommended as an alternative learning model to increase student engagement and motivation.